Musical extracurricular activities and adjustment among children from immigrant families: A 2-year quasi-experimental study - Olivier, Elizabeth; Dupéré, Véronique; Archambault, Isabelle; Meilleur, Marilou; Thouin, Éliane; Denault, Anne-Sophie (Frontiers in Education, 2022)
This quasi-experimental study examines the impact on emotional/behavioral functioning and school experiences of La classe enchantée, a high-quality, non-selective extracurricular music program. The sample includes 72 children (25% in the intervention group, 47% girls, 93% first/second generation immigrants) from one low-income school, followed over two years starting in grade four (Mage = 9.30, SD = .49). Latent Growth Curve models show that, compared to classmates not in the program, children in La classe enchantée progressed more favorably over time on self-reported measures of internalizing symptoms and positive experiences in school. For teacher-rated hyperactivity-inattention and school engagement, the slopes indicated stability over time in both groups, although hyperactivity-inattention tended to improve among those with relatively high initial levels in the intervention group. These results suggest that engagement in quality musical extracurricular activities might boost emotional and school well-being and potentially reduce hyperactivity-inattention among a specific subgroup of children from immigrant families.